Biometrics recognition of newborn: a review - Tiwari S.; Singh R.; Singh S.K.; Kilak A.S.; Alkhayyat A.; Vidyarthi A. (My University, 2025)
The accurate identification and recognition of newborns hold significant importance in ensuring their safety and security within healthcare environments, particularly in hospitals and nurseries. This review article delves into the realm of biometric recognition techniques applied to newborns. The motivation behind this exploration lies in the pressing need for dependable methods that can prevent instances of mix-ups and mismatches, contributing to the overall welfare of infants and peace of mind for caregivers. The review encompasses an analysis of pertinent literature, focusing on authors, methodologies, databases, challenges faced, algorithms employed, performance metrics, and overarching observations. The authors examined a variety of biometric modalities, including footprint recognition based on minutiae features, handprints, facial recognition, and voice recognition. The study considers the distinct challenges associated with newborn biometrics, such as the limited availability of comprehensive databases containing diverse newborn biometric samples. The goal of this review paper is to conduct a thorough analysis of relevant research on biometric recognition of newborns, including the current state-of-the-art, potential challenges, and opportunities. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.